Simulations of explosion-induced damage to underground rock chambers - Ma, G.; Hao, Hong; Wang, F. (Kexue Chubanshe, 2011)
A numerical approach is presented to study the explosion-induced pressure load on an underground rock chamber wall and its resultant damage to the rock chamber. Numerical simulations are carried out by using a modified version of the commercial software AUTODYN. Three different criteria, i.e. a peak particle velocity (PPV) criterion, an effective strain (ES) criterion, and a damage criterion, are employed to examine the explosion-induced damaged zones of the underground rock chamber. The results show that the charge chamber geometry, coupling condition and charge configuration affect significantly the dynamic pressure exerted on the rock chamber wall. Thus the chamber is damaged. An inaccurate approximation of pressure boundary ignoring the influences of these factors would result in an erroneous prediction of damaged area and damage intensity of the charge chamber. The PPV criterion yields the largest damaged zone while the ES criterion gives the smallest one. The presented numerical simulation method is superior in consideration of the chamber geometry, loading density, coupling condition and rock quality. The predicted damage intensity of rock mass can be categorized quantitatively by an isotropic damage scalar. Safe separation distance of adjacent chambers for a specific charge weight is also estimated.